Host-Range Dynamics of Cochliobolus lunatus: From a Biocontrol Agent to a Severe Environmental Threat. (2nd June 2014) - Louis, Bengyella; Waikhom, Sayanika Devi; Roy, Pranab; Bhardwaj, Pardeep Kumar; Sharma, Chandradev K.; Singh, Mohendro Wakambam; Talukdar, Narayan Chandra
Abstract : We undertook an investigation to advance understanding of the host-range dynamics and biocontrol implications of Cochliobolus lunatus in the past decade. Potato ( Solanum tuberosum L) farms were routinely surveyed for brown-to-black leaf spot disease caused by C. lunatus . A biphasic gene data set was assembled and databases were mined for reported hosts of C. lunatus in the last decade. The placement of five virulent strains of C. lunatus causing foliar necrosis of potato was studied with microscopic and phylogenetic tools. Analysis of morphology showed intraspecific variations in stromatic tissues among the virulent strains causing foliar necrosis of potato. A maximum likelihood inference based on GPDH locus separated C. lunatus strains into subclusters and revealed the emergence of unclustered strains. The evolving nutritional requirement of C. lunatus in the last decade is exhibited by the invasion of vertebrates, invertebrates, dicots, and monocots. Our results contribute towards a better understanding of the host-range dynamics of C. lunatus and provide useful implications on the threat posed to the environment when C. lunatus is used as a mycoherbicide.